Revenge of the sequel - Cusick, John (John M.) (Cusick, John (John M.). Dimension why, 2021)
The continuing story of Phineas T. Fogg and Lola Ray, when their seemling straighforward plan to get Lola back home to the twenty-first century leads them on another universe-saving adventure.